Developing and Validating a Rubric for Measuring Skills in Designing Science Experiments for Prospective Science Teachers - Amelia, Rizki Nor; Listiaji, Prasetyo; Dewi, Novi Ratna; Heriyanti, Andhina Putri; Atmaja, Bagus Dwi; Shoba, Tafuz Mahabatis; Sajidi, Imam (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
The Indonesian government mandates that science teachers must have competence in designing science experiments for learning purposes so that science content can be learned optimally by students while preparing them to have the ability to face the 21st century. This is development research that aims to develop a measurement instrument for science experiment design skills for prospective science teachers that meets good psychometric characteristics. The rubric development procedure refers to the Churches rubric development method, which consists of four stages: define, design, do, and debrief, involving 10 experts (lecturers and teachers) and 124 prospective science teachers as research participants. The results of exploratory and confirmatory factor analysis showed that the analytical rubric developed by measuring ten aspects, namely title, research objectives, relevant theories, variables, materials, equipment and instrumentation, method, an appropriate number of data, references, and systematic and technical writing was valid in content (CVI=.96), valid in construct (GFI=.94; RMSEA=.071; NFI=.99; CFI=1.00; PNFI=.91), and reliable (Î±=.968). The use of a standardized rubric certainly allows the assessment to provide consistent, accurate, and objective results and helps students understand what competencies they must achieve.